1990
DOI: 10.1007/bf00169449
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and metabolism of capsaicinoids following intragastric administration in rats

Abstract: This study was performed to examine the metabolism and absorption of intragastrically administered capsaicinoids in the anaesthetized rat. [3H]-dihydrocapsaicin ([3H]-DHC) and unlabelled capsaicin were readily absorbed from the gastrointestinal tract but were almost completely metabolized before reaching the general circulation. A certain degree of biotransformation already took place in the intestinal lumen. Unchanged compounds (identified by chromatography) were present in portal vein blood. There seems to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 13 publications
3
71
2
1
Order By: Relevance
“…It has been reported that dihydrocapsaicin was detected in circulating blood after an intragastric administration. 26) Since Osaka et al have reported that the heat diffusion effect caused by capsaicin was induced via the forebrain, which contains the preoptic area of the hypothalamus considered to be the main integrator site of thermoregulation, 35) the capsaicin-induced heat diffusion effect observed in this study may have been induced after signal transduction from circulating blood capsaicin to the forebrain via some pathway. Caterina et al have shown that a subcutaneous administration of capsaicin decreased the core temperature via TRPV1.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that dihydrocapsaicin was detected in circulating blood after an intragastric administration. 26) Since Osaka et al have reported that the heat diffusion effect caused by capsaicin was induced via the forebrain, which contains the preoptic area of the hypothalamus considered to be the main integrator site of thermoregulation, 35) the capsaicin-induced heat diffusion effect observed in this study may have been induced after signal transduction from circulating blood capsaicin to the forebrain via some pathway. Caterina et al have shown that a subcutaneous administration of capsaicin decreased the core temperature via TRPV1.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to low maximal levels, the plasma half life of capsaicin was quite short: about 25 min following oral administration (Chaiyasit et al 2009) and about 98 min when delivered through the skin (Babbar et al 2009). The rapid clearance of capsaicin is likely related to significant first-pass hepatic metabolism (Donnerer et al 1990;Chanda et al 2008). Adding to the expectation of very modest systemic exposure, the water solubility of capsaicin is very low, in the range of *60 ng/mL under saturated conditions (Turgut et al 2004).…”
Section: Human Exposure and Epidemiological Studiesmentioning
confidence: 99%
“…It has been employed topically to treat various diseases such as rheumatoid arthritis, osteoarthritis, and diabetic neuropathy (2), and to relieve post-operative pain (3)(4)(5)(6). The high degree of firstpass metabolism of intragastric capsaicin and the short halflife of capsaicin by intravenous administration (7.06 min) (7,8) made topical application of capsaicin advantageous. Not only could topical application provide patient convenience and improve patient compliance, it could also circumvent the hepatic metabolism and achieve better bioavailability.…”
Section: Introductionmentioning
confidence: 99%